Historicizing the Uses of the Past Scandinavian Perspectives on History Culture, Historical Consciousness and Didactics of History Related to World War II - Bjerg, Helle; Lenz, Claudia; Thorstensen, Erik (Zeit - Sinn - Kultur, 2011)
This book presents new developments in Scandinavian memory cultures related to World War II and the Holocaust by combining this focus with the perspective of history didactics. The theoretical framework of historical consciousness offers an approach linking individual and collective uses and re-uses of the past to the question how history can and should be taught. It also offers some examples of good practice in this field. The book promotes a teaching practice which, in taking the social constructivist notions of historical consciousness as a starting point, can contribute to self-reflecting and critical thinking - being fundamental for any democratic political culture.